Crosstalk between imbalanced gut microbiota caused by antibiotic exposure and rotavirus replication in the intestine. Issue 1 (January 2023) - Li, Yuhui; Wu, Yifan; Wu, Jie; Yu, Lingling; Li, Xin; Xie, Ke; Zhang, Mingyi; Ren, Lingling; Ji, Yanli; Liu, Yehao
Abstract: Objective: Rotavirus (RV), one of non-enveloped double-strained RNA viruses, can cause infantile diarrheal illness. It is widely accepted that RV is transmitted mainly via feces-oral route. However, infected asymptomatic adults are becoming the source of infection. It is necessary to explore the underlying mechanism of RV replication in adult's intestine. Methods: After recruiting healthy volunteers and RV asymptomatic carriers, we firstly investigated the association of animal-derived food intake with antibiotic level in urine samples. Secondly, we compared the difference in the structure of gut microbiota, and identified the taxa that most likely explained the difference. Finally, we investigated the impact of lipopolysaccharide (LPS), produced by gram-negative bacteria, on RV replication in vivo and in vitro. Results: We found that 10% of participants were RV asymptomatic carriers in our study. High intake of animal-derived food was positively correlated to antibiotic level in urine samples. The disrupted gut microbiota in RV carriers was characterized by high abundance of antibiotic resistant gram-negative bacteria and high level of LPS. The disrupted gut microbiota caused by penicillin treatment was benefit to RV replication in vivo. LPS enhanced RV thermal stability in vitro. Conclusions: Our findings suggest that the imbalanced gut microbiota caused by antibiotic exposure plays an important role in RV replication, and brings risk to health complications.